International joint ventures : partnering skills and cross-cultural issues - Buckley, Peter J. (2002)
Presents a matrix to examine the four categories of skill in the context in which each is used. Offers results that have important implications for the management of international joint ventures with regard to the selection and training of managers and the inculcation of the skills required for each level of operation.